Singapore public transport system in focus : transport in Nanyang Technological University. - Soh, Wai Kien. (2011)
A good transport system is vital for the smooth and efficient transport of students in and out of a school campus. This is especially so with Nanyang Technological University (NTU) being a campus with an undergraduate population of more than 20000. This research study aims to present an in dept evaluation of the transport system in NTU. The users’ perspectives are captured through questionnaires. On the other hand, field collection of data was also conducted to provide a clearer idea of the actual situation on the ground. Through this study, we aim to highlight some problems in the transport system in NTU, analyse the behaviour of students commuting in and out of NTU, and also to provide recommendations to improve the overall transport system. With this, we hope that the resources of the transportation companies can be better allocated and put to more efficient use in meeting the transportation needs of NTU.